2019
DOI: 10.1177/1534650119834359
|View full text |Cite
|
Sign up to set email alerts
|

Written Exposure Therapy: The Case for Latinos

Abstract: Despite the substantial impact of trauma and subsequent posttraumatic stress in the Latino population, Latinos often underutilize services to address symptoms. Furthermore, research is still lacking regarding the effectiveness of evidence-based treatments, specifically for Latinos. We review the case of a 29-year-old Latina diagnosed with posttraumatic stress disorder (PTSD) who presented with intrusive memories, nightmares, and negative affect. The client’s progress in treatment was hindered by extreme emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This necessitated careful management by the therapist (D.D.B.) by reexplaining the function and benefit of imaginal exposure and mitigating the effect of avoidance during treatment (see Benuto & Bennett, 2019). Therefore, the subjective experience of improvement by a participant requires tactful and critical engagement to rule out any form of avoidance masked as improvement.…”
Section: Treatment Implications Of the Casementioning
confidence: 99%
“…This necessitated careful management by the therapist (D.D.B.) by reexplaining the function and benefit of imaginal exposure and mitigating the effect of avoidance during treatment (see Benuto & Bennett, 2019). Therefore, the subjective experience of improvement by a participant requires tactful and critical engagement to rule out any form of avoidance masked as improvement.…”
Section: Treatment Implications Of the Casementioning
confidence: 99%
“…Although certain ethnoracial minority groups have high levels of trauma exposure and various trauma types, including exposure to war‐related trauma (Roberts, Gilman, Breslau, Breslau & Koenen, 2011), natural disasters (Bryant, 2006; Udomratn, 2008), traumatic experiences before immigrating to the United States or during the immigration process (Benuto & Bennett, 2019; Cleary, Snead, Dietz‐Chavez, Rivera, & Edberg, 2018), violence (Gonzalez, Benuto, & Casas, 2018; Roberts et al., 2011) and racial discrimination (Pérez, Fortuna, & Alegría, 2008), to name a few, there is a discrepancy between a diagnosable mental health condition and behavioral health service use (Le Meyer, Zane, Cho & Takeuchi, 2009). Mendoza and colleagues (2012) posited that underrepresentation may be a cultural barrier that restricts the patient from fully expressing symptoms in a way that the clinician can understand, contributing to possible underdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…WET has demonstrated efficacy in waitlist-controlled trials and noninferiority trials (Sloan et al, 2012(Sloan et al, , 2018, has shown long-term reductions in PTSD symptoms after completion of all WET sessions (Thompson-Hollands et al, 2018), and has exhibited significantly lower dropout rates during treatment compared to other empirically supported treatments for PTSD (6% for WET versus 39% for CPT; Thompson-Hollands et al, 2018). Additionally, Benuto and Bennett (2019) successfully implemented WET in one case study with a Latinx immigrant, offering a highly preliminary indication of potential feasibility and effectiveness. Similarly, preliminary research from our team has demonstrated significant PTSD and depression symptom reduction in a Latinx immigrant sample, while qualitative data also highlighted that participants largely reported perceiving WET as beneficial (Andrews et al, 2021).…”
Section: Written Exposure Therapy Overviewmentioning
confidence: 99%